Agricultural commodities : profiles and relevant WTO negotiating issues (FAO RomeIT, 2002)
Presents brief profiles for each of the major traded agricultural commodities. Provides a convenient summary of the most important economic and market characteristics of each commodity. Provides brief assessments for sixteen commodities or commodity groups of the status of implementation of various policy measures disciplined under the Uruguay Round Agreement on Agriculture, and of issues arising in the new round of multi-lateral trade negotiations.
Prepared as a background document for the Consultation on Agricultural Commodity Price Problems, 25-26 March 2002, Rome